Analisis Sekolah Unggul Ditinjau dari Indikator Mutu Sekolah - Yuliani Fitri; Rusdinal Rusdinal; Nurhizrah Gistituati (Journal on Education, 2024)
This research aims to describe the school quality indicators that must be met to make a school superior. This type of research is descriptive qualitative with a literature study method. Information obtained from relevant sources comes from books, research results, journals, mass media and others related to discussions about superior schools as seen from school quality indicators. From the results of the analysis it can be concluded that a school is said to be superior if it meets all school quality indicators.